WHY WORSHIP GOD?. Issue 46 (6th April 2017) - Cahn, Steven M.
Abstract : Assuming God exists, should we worship God? This article contends that even if God is omniscient, omnipotent and omni-benevolent, and created and sustains the world, we should adopt the attitude towards God exhibited by Abraham in Chapter 18 of Genesis. There, having been informed of God's willingness to destroy Sodom, Abraham persuades God that if the city contains ten innocent inhabitants, justice requires the plan to be altered. The story undermines the divine command theory of morality, demonstrates that God is subject to change, and suggests that God is prepared to be challenged rather than worshipped.